Motives of Creativity and Inspiration in al-Maqri’s Scientific (Linguistic and Literary) Production: An Analytical Reading within its Historical and Cultural Context (Journal of Informatics Education and Research, 2025)
This research paper aims to define the nature of creativity and inspiration as conceived by the great masters and distinguished scholars, and to examine the extent of intellectual productivity they left behind as a cultural heritage that enriches the Arab-Islamic library. It further explores how researchers have discussed the relationship between the foundations of the concepts of creativity and inspiration, intellectual abundance, and the process of creation in al-Maqri’s works, and how this becomes evident and manifest in his scientific writings. These writings served as pillars, foundations, and references upon which researchers rely in their intellectual and scientific investigations. The paper also compares the originality of these creative contributions and the quality of their ideas within a framework of questions upon which the objectives of this study are built—questions concerning those who create events, those who witness them, and those who inquire about them. Thus, it raises the central question: Where did al-Maqri’s creativity manifest in his scientific writings? What are its features? And in what ways did it appear?